Dealing with Competing Project Management Values under Uncertainty: the Case of RandstadRail - Leijten, Martijn; Koppenjan, Joop; Heuvelhof, Ernst ten; Veeneman, Wijnand; Voort, Haiko van der (European Journal of Transport and Infrastructure Research, 2010)
Due to the uncertainty involved in many complex infrastructure engineering projects, it is not always possible for managers to establish detailed terms of reference at the departure. Although the flexibility of ‘open’ terms of reference is often indispensible, it makes the arrival at a successful outcome much of a gamble. Complex infrastructure construction projects often include the tension that the values and interests of clients and functional managers diverge or even contradict each other. This is especially evident when managing the project management values of time, cost, scope and quality in relation to each other while the results of trade-offs and decisions can not be predicted. Client’s administrators defend objectifiable, instrumental values, while functional managers have an interest in relaxing them in order to realise the project. If these two contradictory sets of interests are not recalibrated, either the values are not met, or trade-offs may be made in an uncontrolled way, which can lead to suboptimisations or even project failure. Using RandstadRail as an example, this paper will show the problems that may occur in such situations and how unmanageability arises. A few lessons are derived to provide entrance to better manageable practice.